PENGARUH STRUKTUR SISTEM PENGENDALIAN INTERN TERHADAP KINERJA PERKREDITAN PADA BANK PERKREDITAN RAKYAT PD. BPR BKK BOYOLALI - Muhammad Rofiq Sunarko, Mulyanti, Djoko Kristianto & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze the significance of the influence of the control environment, risk assessment, control activities, information and communication, and monitoring the credit performance on Rural Bank PD. BPR BKK Boyolali. The research method using the case study method, the type of data used quantitative and qualitative data, the data source used primary data and secondary data. Data collection methods used documentation. Data analysis technique used to test the research instrument, the classical assumption test, multiple linear regression analysis, t-test, F and coefficient of determination. In conclusion: 1) There is a positive and significant effect of the control environment, risk assessment, control activities, information and communication, and monitoring of Rural Banks credit in PD. BPR BKK Boyolali. 2) There is significant influence control environment, risk assessment, control activities, information and communication, as well as the simultaneous monitoring of the performance of rural banks credit in PD. BPR BKK Boyolali.Keywords: control environment, risk assessment, control activities, information and communication, monitoring, credit performance